Knowledge integration in new product development: the FIAT Autocase. (1st January 2003) - Becker, Markus C.; Zirpoli, Francesco
The article analyses the organisation of the new product development process at FIAT Auto with a particular focus on knowledge used in this process. The knowledge dimension emerges as important in the new product development process in particular because of the outsourcing of design tasks. Such outsourcing not only solves the problems of cutting costs and reducing lead times, but also raises the problem that the knowledge required in the new product development process is spread more widely across the supply chain. Subsequently, it needs to be (re-)integrated and coordinated in order to make for a whole. How do car makers go about organising the integration and co-ordination of knowledge required in the new product development process, reinforced by strong outsourcing? The article casts some light on this question from the case of FIAT Auto, reporting insights from a longitudinal study that spans the years 1991–2002.